Politics and International Relations. Issue 4 (4th July 2021) - Simon, Steven
Abstract : You Say You Want a Revolution? Radical Idealism and Its Tragic Consequences Daniel Chirot. Princeton, NJ: Princeton University Press, 2020. £25.00/$29.95. 192 pp. Bullets Not Ballots: Success in Counterinsurgency Warfare Jacqueline L. Hazelton. Ithaca, NY: Cornell University Press, 2021. $39.95. 220 pp. Coping with Defeat: Sunni Islam, Roman Catholicism, and the Modern State Jonathan Laurence. Princeton, NJ: Princeton University Press, 2021. £28.00/$35.00. 606 pp. The Last Shah: America, Iran, and the Fall of the Pahlavi Dynasty Ray Takeyh. New Haven, CT: Yale University Press, 2021. £25.00/$32.50. 336 pp. Escape from Rome: The Failure of Empire and the Road to Prosperity Walter Scheidel. Princeton, NJ: Princeton University Press, 2019. £28.00/$35.00. 670 pp.